Spatial Patterns of Environmental Sanitation Factors as Determinants of Toddlers' Diarrhea in Pauh District, Padang City in 2021 - Andika Agus Iryanto; Yura Witsqa Firmansyah; Wahyu Widyantoro; Annisa Zolanda (Universitas Airlangga, 2022)
Introduction: The Padang City Health Office reported 9,452 diarrhea cases in 2019, 2,248 in toddlers. The Pauh District reported 413 diarrhea cases, 110 of which occurred in toddlers. Spatial analysis was used to assess environmental sanitation as determinant of toddlers' diarrhea incidence in Pauh District, Padang City. Methods: This observational study used a cross-sectional approach. The population was 4,653 toddlers, and the sample was 100 toddlers. The independent variables in this study include environmental sanitation factors such as the quality of clean water (presence of Escherichia coli), the condition and quality of the waste container, the quality and condition of sewerage, and the density of flies in the trash and household sewerage. The spatial analysis used was Moran Index I to examine the distribution pattern of variables. Results and Discussion: The incidence of diarrhea in toddlers, unstandardized household waste containers, unqualified waste sewerage, high fly density in household trash bins, and high fly density in sewerage was randomly distributed with a Moran index consecutively -0.130524; 0.315524; 0.153129; -0.174424; -0.025798. Then, clean water quality, waste management, and sewerage conditions that did not meet the requirements were randomly distributed with a Moran index of -0.158512; -0.160688; -0.117502. Conclusion: The spatial pattern of environmental sanitation factors as determinants of the incidence of diarrhea in toddlers was randomly distributed, and there was no autocorrelation found among the villages in Pauh District.